Development of Social Interaction Learning Model in Instilling the Value of Discipline for Children - Roza, Ahmad Subhan; Priyantoro, Dian Eka; Harya, Trisna Dinillah (Journal of Education and Teaching Learning, 2024)
Humans need the value of disciplined character in order for other positive character traits to emerge. Due to the high number of student actions that defy established disciplinary guidelines, it is crucial to reinforce the necessity of discipline in schools.This research aims to develop a Social Interaction Learning model in instilling discipline values in children. The research results are in the form of a social interaction learning model in instilling discipline values in children, namely: 1) The social interaction-based learning model is appropriate for instilling and improving the value of discipline in fourth grade elementary school children. 2) The social interaction-based learning model is significant and feasible in instilling discipline values in fourth grade students at Elementary School 3) An effective social interaction-based learning model for instilling the value of discipline in fourth grade elementary school children. Social Interaction could be one of the model to instill students dicipline.